Multipurpose fabricated bubble wrapping plastic liner (BW-LINER) for general engineering application / Nur Azwa Muhamad Bashar ... [et al.] - Muhamad Bashar, Nur Azwa; Rahman, Nur Raihan Sofiyah; Md Isa, Nur Hanem Syarhida; Alias, Salina; Abdul Talib, Suhaimi (2020)
Non-Biodegradable Plastic source namely Bubble Wrapped Plastic (BWP) mainly in the packaging industry has leading to the landfilling problems. Instead of landfilling, burning process can be the options. However, this kind of methods has contributing to the climate change impacts including ozone depletion due to the carbon dioxide (CO2) increments. This study provides solution to the raised problem where the BWP itself is used as engineering layer in the construction of several infrastructure projects including drainage, road works and sanitary landfill (waste disposal site). This study proposed on the usage of fabricated BW-Liner as an alternative to conventional plastic sheets namely Geo-Membrane (GM). Raw bubble wrapped plastic was fabricated from a single layer into an engineered layer I with 30 layers of single plastic (4-mm thickness) and applied with hot-pressing technique to increase the strength in between the plastic surface. The single and fabricated engineered layer I were then tested for chemical (Thermogravimetric analysis - TGA) and mechanical (Tensile strength analysis) characteristics. Obtained results from TGA analysis shown fabricated BW-Liner and GM undergoing thermal degradation when temperature reached 480oC to 490oC. Findings from tensile (strength and stress) analysis shows that BWLiner can withstand the higher forces at 185 N for 4-mm thickness while GM at 213 N at 2-mm thickness. The proposed BW-Liner can promote sustainable solution to landfilling problems by recycling the NBP waste and provide option to the industrial practitioner in term of using low-cost added material.